asst6-f11_solutions

# asst6-f11_solutions - MATH 137 Assignment #6 Solutions 1....

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MATH 137 Assignment #6 Solutions 1. a) lim x e sin x- 1 x- To express this as a derivative, notice that since sin = 0, we can express the limit as lim x e sin x- e sin x- = lim x f ( x )- f ( ) x- = f ( ) where f ( x ) = e sin x The derivative of f ( x ) is calculated using the chain rule: f ( x ) = e sin x cos x = f ( ) = e sin cos = e (- 1) =- 1 Therefore, lim x e sin x- 1 x- = f ( ) =- 1 b) lim x 2- 5 32- x x If we let f ( x ) = 5 32- x , we notice that f (0) = 2 and the limit is of the form lim x 2- 5 32- x x = lim x f (0)- f ( x ) x- =- lim x f ( x )- f (0) x- =- f (0) Differentiating f ( x ) = 5 32- x : f ( x ) = 1 5 (32- x )- 4 / 5 (- 1) =- 1 5 (32- x )- 4 / 5 = f (0) =- 1 5 (32)- 4 / 5 =- 1 5 1 32 4 / 5 =- 1 80 lim x 2- 5 32- x x =- f (0) = 1 80 2. a) If H ( x ) = g ( f ( x )), then H ( x ) = g ( f ( x )) f ( x ). Thus, T ( x ) = H ( a ) + H ( a )( x- a ) = g ( f ( a )) + g ( f ( a )) f ( a )( x- a ) b) Since the tangent line to f at a is given by L ( x ) = f ( a ) + f ( a )( x- a ), and the tangent line to g at b is given by M ( y ) = g ( b ) + g ( b )( y- b ), then M ( L ( x )) = g ( b ) + g ( b )( L ( x )- b ) = g ( b ) + g ( b )( f ( a ) + f ( a )( x- a )- b ) 1 c) Substituting...
View Full Document

## This note was uploaded on 12/31/2011 for the course MATH 135 taught by Professor Andrewchilds during the Fall '08 term at Waterloo.

### Page1 / 5

asst6-f11_solutions - MATH 137 Assignment #6 Solutions 1....

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online